Characterization of fluorine-based hydrophobic coating towards water aging application - Che Ibrahim, Mohd Naqiudin (2018)
In the present world, coating technology is a reliable and effective modern technology utilize in wide range of applications in various industry including solar panel, eyewear, building glass panel, and many more. The coating applied to surface of these materials required a specific requirement such as water resistance, good adhesive strength, and optically transparent, mainly for physical and chemical protection. The afore mentioned requirements demand coating’s material with water repellent properties, low scattering/diffusion coefficient, and good molecular force attraction towards glass surfaces. This can be realized by tailoring the molecular structure and bonding properties of the where the protection can be sustained. This work details with coating solution preparation adopted to produce roughened surface with water repellent ability aiming to enhance the surface physical and chemical protection. This thesis focuses the coating process using spray coating technique with tetraethyl orthosilicate (TEOS) and heptadecafluorodecyltrimethoxysilane (HFTMS). The coating properties such as water contact angle, surface morphology, transparency, adhesiveness, and refractive index of the coating are characterized carefully by using contact angle instrument, atomic force microscopy (AFM), UV-Vis spectrometer, scratch test, and ellipsometer instruments. The coating materials are found to have very significant effect on water resistant ability where the present of water repellent agent of HFTMS, with the present of fluorine in the coating materials has been found to produce higher contact angle value. In addition, increasing the surface roughness of the coating, by manipulating the spray setting and water aging cycles, has been found to enhance further the water contact angle of the coating. Thus, the optimized surface roughness and contact angle have been chosen in order to obtain the best water-resistant properties with higher water contact angle even after water aging process. Findings from AFM measurement confirmed that higher surface roughness coating is achieved after the samples have been through water aging process which promotes the coating material molecules to accumulates and bulking to each other. Other than that, the result from UV-Vis spectrometer has shown that the transmission coefficient of the coated materials is consistent along all samples even sprayed at different setting and after going through water aging process. Interestingly, the refractive index of TEOS samples shows a constant value even after the dipping cycles. This study shows that the present of fluorine particle in the water resistive agent has introduced the water resistance properties with high contact angle for the sample. Furthermore, controlling the surface roughness by manipulating the spray setting and water aging process, the water contact angle can be increased. In addition, changing the spray process parameter and water aging process have no influence on the optical transparency of the coating. However, the refractive index of the samples varies as the material is reported to contain porous structure smaller than the light wavelength. Therefore, this study shows the use of fluorine in coating material as water repellent agent can permits better water resistive properties when exposed to water molecules. After the sample characterizations and analysis, it was found that sample with alumina number of particles 0.006311849 per um₂ has shown good properties of hydrophobicity in long term period, and meanwhile, sample with alumina number of particles 0.004176432 per um₂ has shown good hydrophobicity in short term period.